(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic brought a series of consequences for the world population, including the interruption of the face-to-face activities of Brazilian universities. It´s understood that changes in the lifestyle of students of undergraduate nursing courses may occur, due to social isolation. The aim of this study was to analyze the factors associated with the lifestyle of nursing students during the COVID-19 pandemic. This is a cross-sectional study that collected data through an online questionnaire sent to nursing students at a public university in the interior of Bahia. There were 86 students who responded voluntarily to two instruments: one on sociodemographic, behavioral emotional and attitudinal data (self-reported), also related to the COVID-19 pandemic and the Nola Pender lifestyle inventory. Central tendency and dispersion measures were developed. The data were described using absolute and relative frequencies, means and standard deviations, as well as minimum and maximum values. The lifestyle was analyzed using the “Nola Pender Lifestyle Profile” scale and non-parametric tests were used. The study showed correlations between the variable gender and nutrition, religion and social support, if you are caring for someone during the pandemic and social support, if you are practicing physical activity and physical exercise and if you are having healthy habits in the COVID-19 pandemic with support Social. In this sense, it is recommended a close look at university institutions in relation to the promotion of care and self-care by university students.